Updates in the chronic kidney disease-mineral bone disorder show the role of osteocytic proteins, a potential mechanism of the bone—Vascular paradox, a therapeutic target, and a biomarker - Williams, Matthew J.; White, Sarah C.; Joseph, Zachary; Hruska, Keith A. (Frontiers in Physiology, 2023)
The chronic kidney disease-mineral bone disorder (CKD-MBD) is a complex multi-component syndrome occurring during kidney disease and its progression. Here, we update progress in the components of the syndrome, and synthesize recent investigations, which suggest a potential mechanism of the bone-vascular paradox. The discovery that calcified arteries in chronic kidney disease inhibit bone remodeling lead to the identification of factors produced by the vasculature that inhibit the skeleton, thus providing a potential explanation for the bone-vascular paradox. Among the factors produced by calcifying arteries, sclerostin secretion is especially enlightening. Sclerostin is a potent inhibitor of bone remodeling and an osteocyte specific protein. Its production by the vasculature in chronic kidney disease identifies the key role of vascular cell osteoblastic/osteocytic transdifferentiation in vascular calcification and renal osteodystrophy. Subsequent studies showing that inhibition of sclerostin activity by a monoclonal antibody improved bone remodeling as expected, but stimulated vascular calcification, demonstrate that vascular sclerostin functions to brake the Wnt stimulation of the calcification milieu. Thus, the target of therapy in the chronic kidney disease-mineral bone disorder is not inhibition of sclerostin function, which would intensify vascular calcification. Rather, decreasing sclerostin production by decreasing the vascular osteoblastic/osteocytic transdifferentiation is the goal. This might decrease vascular calcification, decrease vascular stiffness, decrease cardiac hypertrophy, decrease sclerostin production, reduce serum sclerostin and improve skeletal remodeling. Thus, the therapeutic target of the chronic kidney disease-mineral bone disorder may be vascular osteoblastic transdifferentiation, and sclerostin levels may be a useful biomarker for the diagnosis of the chronic kidney disease-mineral bone disorder and the progress of its therapy.